The Effect of Internalized Stigma on Psychological Resilience in People with Mental llness - Funda Kavak; Tülay Yıldırım Üşenmez (Ebelik ve Sağlık Bilimleri Dergisi, 2025)
Objective: The purpose of the present study was to evaluate the effect of internalized stigma on psychological resilience in people with mental illness.Methods: The present study was a cross-sectional type. A hundred-sixty five (165) people with mental illlness were included in the study. Descriptive Features Form, Internalized Stigma of Mental Illness Inventory (ISMI), and Brief Resilience Scale (BRS) were utilized to gather data.Results: There was a statistically negative strong relationship between ISMI and BRS (r=-0.803, p